Sociological theory - Ritzer, George (New York : McGraw-Hill, 1992)
"Sociological theory is undergoing dramatic changes and those changes are reflected in the substantial restructuring of the third edition of this book. The most obvious change in this edition is in the overall structure if the book. The previous edition was divided into two parts- classical and contemporary sociological theory. In this edition there are three parts- classical sociological theory, the major schools of sociological theory, and the most recent developments in sociological theory discussed under the headings of integration and synthesis."
Includes bibliographical references.
English text.
Keywords: Sociology; Sociologists -- Biography